A Young Woman's Experience of Living with Hemophilia: A Qualitative Case Study - Samira Foji; Akram Sanagoo; Leila Jouybari (Kerman University of Medical Sciences, 2021)
Introduction: Hemophilia is a genetic disorder inherited in an X-linked fashion and accompanied with dysfunctional coagulation factors 8 (hemophilia type A) or 9 (hemophilia type B). Hemophilia has a dramatic effect on the quality of life of patients. The objective of this study was to describe a young woman's experience of living with hemophilia from childhood to motherhood. Methods: This qualitative study explored a 32-year-old woman's experience of living with hemophilia. Data were collected using interactive semi-structured interviews. Date analysis was performed using a phenomenological approach. Member check and researcher triangulation were used in data analysis to ensure the accuracy of the study. All ethical principles were considered in this research. Results: Data analysis revealed four main themes, including "being involved in treatment", "suffering", "fear and worry", and "acceptance of being different", and eight subthemes, including "pity and humiliation", "social stigma", "fear of marriage and motherhood", "fear of continuing education", "limiting one's relationships", "getting to know others with the same disease", "accepting fate", and "independence". Conclusion: This study presented the point of view of a young woman with hemophilia regarding her challenges as well as physical, psychological, and social sufferings from childhood to adulthood